Hepatitis Delta Virus (HDV) and Delta-Like Agents: Insights Into Their Origin - Netter, Hans J.; Barrios, Marilou H.; Littlejohn, Margaret; Yuen, Lilly K. W. (Frontiers in Microbiology, 2021)
Hepatitis delta virus (HDV) is a human pathogen, and the only known species in the genus Deltavirus. HDV is a satellite virus and depends on the hepatitis B virus (HBV) for packaging, release, and transmission. Extracellular HDV virions contain the genomic HDV RNA, a single-stranded negative-sense and covalently closed circular RNA molecule, which is associated with the HDV-encoded delta antigen forming a ribonucleoprotein complex, and enveloped by the HBV surface antigens. Replication occurs in the nucleus and is mediated by host enzymes and assisted by cis-acting ribozymes allowing the formation of monomer length molecules which are ligated by host ligases to form unbranched rod-like circles. Recently, meta-transcriptomic studies investigating various vertebrate and invertebrate samples identified RNA species with similarities to HDV RNA. The delta-like agents may be representatives of novel subviral agents or satellite viruses which share with HDV, the self-complementarity of the circular RNA genome, the ability to encode a protein, and the presence of ribozyme sequences. The widespread distribution of delta-like agents across different taxa with considerable phylogenetic distances may be instrumental in comprehending their evolutionary history by elucidating the transition from transcriptome to cellular circular RNAs to infectious subviral agents.